Advances and challenges in biosensor-based diagnosis of infectious diseases - Sin, Mandy LY (2014)
Rapid diagnosis of infectious diseases and timely initiation of appropriate treatment are critical determinants that promote optimal clinical outcomes and general public health. Conventional in vitro diagnostics for infectious diseases are time-consuming and require centralized laboratories, experienced personnel and bulky equipment. Recent advances in biosensor technologies have potential to deliver point-of-care diagnostics that match or surpass conventional standards in regards to time, accuracy and cost. Broadly classified as either label-free or labeled, modern biosensors exploit micro- and nanofabrication technologies and diverse sensing strategies including optical, electrical and mechanical transducers. Despite clinical need, translation of biosensors from research laboratories to clinical applications has remained limited to a few notable examples, such as the glucose sensor. Challenges to be overcome include sample preparation, matrix effects and system integration. We review the advances of biosensors for infectious disease diagnostics and discuss the critical challenges that need to be overcome in order to implement integrated diagnostic biosensors in real world settings.